2012
DOI: 10.1246/bcsj.20110203
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of π Molecular Orbitals in Planar Boron Clusters

Abstract: The energy of the lowest π molecular orbital in a planar boron cluster can be estimated from the connectivity of constituent boron atoms, or the mean valency of the boron atoms. Low-energy π molecular orbitals were then predicted to occur in all realistic planar polycyclic boron clusters. In fact, all such boron clusters studied have one or more π molecular orbitals with two or more π electrons. They are aromatic with positive topological resonance energies. π Conjugation and aromaticity must be totally or par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The latter become prevalent in the larger nearly planar boron clusters. Even more interesting is the suggested relationship of these planar networks of boron triangles to the planar networks of carbon hexagons found in benzenoid hydrocarbons . Thus, low-energy and experimentally realized B 12 , B 17 – , B 18 , B 22 – , and B 23 – in the gas phase have been considered as analogues of benzene, naphthalene, , coronene, anthracene, and phenanthrene, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter become prevalent in the larger nearly planar boron clusters. Even more interesting is the suggested relationship of these planar networks of boron triangles to the planar networks of carbon hexagons found in benzenoid hydrocarbons . Thus, low-energy and experimentally realized B 12 , B 17 – , B 18 , B 22 – , and B 23 – in the gas phase have been considered as analogues of benzene, naphthalene, , coronene, anthracene, and phenanthrene, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Even more interesting is the suggested relationship of these planar networks of boron triangles to the planar networks of carbon hexagons found in benzenoid hydrocarbons. 25 − in the gas phase have been considered as analogues of benzene, naphthalene, 26,27 coronene, 27 anthracene, 28 and phenanthrene, 28 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of three-center two-electron (3c-2e) bond, as proposed by Lipscomb to elucidate the structures of boranes, is a cornerstone in modern chemical bonding theory. 1 Extensive recent studies on elemental boron clusters have revealed planar or quasi-planar clusters, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] borospherenes, [21][22][23] and borophenes. [24][25][26][27] Their chemical bonding is governed by p/s aromaticity, antiaromaticity, conflicting aromaticity, and multifold aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…Boron and boron-based clusters have attracted much attention in the past 20 years owning to their interesting physical and chemical properties. Experimental and theoretical studies over the last decades have demonstrated that positively charged boron clusters are shown to become 3D at B 16 + , [33][34][35][36] while negatively charged and neutral boron clusters are still planar at B 23 − and B 19 , [37][38][39][40][41][42][43][44][45][46][47][48][49] respectively, except for B 14 . 50 Two types of delocalized bonding -the in-plane σ and the out-of-plane π bonding are found in the planar boron clusters, each of which follows the (4n + 2) Huckel rule for aromaticity.…”
Section: Introductionmentioning
confidence: 99%